Unplanned stopping strategy in individuals with mild cognitive impairment - Boripuntakul S. (2017)
© 2016 Walailak University. All rights reserved. Individuals with Mild Cognitive Impairment (MCI) demonstrate changes in cognitive and gait functions. Gait termination requires higher cognitive integration compared to steady-state walking due to the increased stability needed during a transient period. It is possible that the capability to terminate gait in older adults with MCI would be compromised. Therefore, this study aimed to compare gait termination parameters between older adults with MCI and without MCI. Gait termination parameters (i.e., the number of steps taken to stop, total stopping distance, and total stopping time) were assessed in 30 older adults with MCI and in 30 cognitively intact controls. The Mann-Whitney U test revealed that the MCI group required more steps to stop compared to the control group (MCI group = 2.02 ± 0.40 steps; control group = 1.91 ± 0.36 steps, p = 0.05). These findings suggest that older adults with MCI adopt a more conservative strategy by employing additional steps for terminating gait. Poor executive function may affect gait termination performance in older adults with MCI.